Update on Basal and Bolus Insulin Therapies - Vinall, Phil (MD Conference Express, 2012)
Insulin is released continuously by the pancreas at a nearly constant rate between meals and in the fasting state (basal insulin secretion). This article discusses the data on various basal insulins, as well as evolution of rapid-acting insulin, limitations of current insulin preparations, and pipeline products.